PTU-285 Early in-patient management of alcohol-related liver disease: results of a liver care bundle to improve quality of care. (22nd June 2015) - Huang-Doran, I; Mason, C; Mcphail, M; Peake, S; Monahan, K; Collins, C
Abstract : Introduction: The incidence of Alcohol Related Liver Disease (ARLD) is rising in the UK, as is its associated mortality. A recent National Confidential Enquiry into Patient Outcome and Death (NCEPOD) report highlighted recurring deficiencies in the care of ARLD in UK hospitals and the British Gastroenterological Society provided guidance in the treatment of these patients during acute hospital admissions. Method: Between 1 August 2013 and 31 October 2013, consecutive admissions of patients with ARLD to a district general hospital were identified from discharge and mortality data. A liver care bundle (LCB) using NCEPOD recommendations was generated and case notes analysed prior to institution of this LCB and re-audited following its inception from 1 April 2014 to 31 July 2014. Electronic referrals to specialist gastroenterology and dieticians formed part of the LCB as well as a checklist of actions for the admitting physician. Results: 20 patients (median age 51 (28–67) years) were identified initially with ARLD, of which 13 (65%) were male. Median Model for End-stage Liver Disease (MELD) score was 14 (range 6–35). Post LCB institution a further cohort of 25 patients studied was matched for age (59 (32–79) years, sex (13/25 (52% male) and MELD score (13 (6–40)). Inpatient mortality was 7/20 (35%) prior and 2/23 (9%) post LCB (p = 0.065). All patients were screened for ongoing alcohol use and in 65% a withdrawal regime was prescribed. Only 1/20 (5%) had dietician input in the first 48 h rising to 11/25 (44%) post LCB institution (p < 0.001). In all patients with ascites in the presence of acute kidney injury, diuretics were discontinued in both cohorts. In 92% of cases of ascites, diagnostic parascentesis was performed, however blood cultures were performed on admission in only 6/20 (30%) initially rising to 40% post LCB. 13/20 of patients (65%) had consultant review within 12 h pre LCB with 18/25 (72%) post LCB. The proportion of patients receiving specialist review by a gastroenterologist within 72 h rose from 45% to 54% following LCB use. Conclusion: Instituting a liver care bundle for the management of alcohol related liver disease at our centre improved both the quality of care and outcome from patients admitted during acute decompensation, particularly related to early specialist review. Initiation of bundles of care in liver disease requires close collaboration between specialist medical services and allied health professionals such as dieticians to optimise patient care. Disclosure of interest: None Declared.